On Groups with Minimality Condition for Noninvariant Abelian pd-Subgroups - Lyman, F. N. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study properties and the structure of non-Abelian groups with minimality condition for non-invariant Abelian pd-subgroups in the case where they do not satisfy the minimality condition for Abelian pd-subgroups. We prove the solvability of these groups and establish relations with non-Abelian groups in which all infinite Abelian pd-subgroups are invariant.